The performance of transnational corporations: Evidence for the manufacturing industry in Chile - Sebastián M. Vergara (CEPAL Review, 2013)
This article analyses the performance of transnational corporations in Chilean manufacturing industry. The findings show that while the productivity of subsidiaries of foreign-owned firms is higher than that of local firms, the same is not true of productivity growth. They also show that there are no significant differences in market survival rates between transnational corporations and local firms. However, firms under mainly foreign ownership that are small and have low productivity are more likely to exit the market, displaying more footloose behaviour than their local counterparts. This is associated with lower levels of profitability for this group of transnational firms. Lastly, the findings suggest that transnational corporations are not always more profitable than local firms. Furthermore, they seem able to exploit their advantages over the latter only in the higher quantiles of the profitability distribution.